Chemical Approaches to Carbon‐Based Metal‐Free Catalysts - Liu, Dong; Dai, Liming; Lin, Xuanni; Chen, Jian‐Feng; Zhang, Jian; Feng, Xinliang; Müllen, Klaus; Zhu, Xiang; Dai, Sheng (Advanced materials (Weinheim), 2019)
Highly active and durable catalysts play a key role in clean energy technologies. However, the high cost, low reserves, and poor stability of noble‐metal‐based catalysts have hindered the large‐scale development of renewable energy. Owing to their low cost, earth abundance, high activity, and excellent stability, carbon‐based metal‐free catalysts (CMFCs) are promising alternatives to precious‐metal‐based catalysts. Although many synthetic methods based on solution, surface/interface, solid state, and noncovalent chemistries have been developed for producing numerous CMFCs with diverse structures and functionalities, there is still a lack of effective approaches to precisely control the structures of active sites. Therefore, novel chemical approaches are needed for the development of highly active and durable CMFCs that are capable of replacing precious‐metal catalysts for large‐scale applications. Herein, a comprehensive and critical review on chemical approaches to CMFCs is given by summarizing important advancements, current challenges, and future perspectives in this emerging field. Through such a critical review, our understanding of CMFCs and the associated synthetic processes will be significantly increased. Various synthetic strategies, including solution, surface/interface, solid‐state, and noncovalent chemistries, have been developed for producing numerous carbon‐based metal‐free catalysts (CMFCs) with appropriate functionalities for specific reactions. A comprehensive and critical review of chemical approaches to CMFCs is provided by summarizing recent advancements in this emerging field, along with current challenges and future perspectives.